Secured Transmission of Image/Video by Performing Reversible Color Transformation. (2016) - Issac, Gija Susan; Jose, Jobi
Abstract: A new secured image/video transmission technique is proposed in this paper. Here video is considered as a sequence of frames. The secret image is automatically transformed into a secret-fragment visible mosaic image. This image looks similar to a randomly selected target image. The target image is used to cover or hide the secret image. Also relevant information for reconstructing the secret image is embedded on the mosaic image by a loss less data hiding scheme using a key. The secret image is divided into cells and the color characteristics of each cell are transformed to that of the divided target blocks. In order to reconstruct the secret image losslessly, skilful techniques are designed to conduct the color transformation process. Performance evaluations of the proposed method shows improved peak signal to noise ratio compared with the existing method.